ANALISIS KEPUTUSAN PEMBELIAN JASA HOTEL BERBASIS SYARIAH PADA SITUS E-COMMERCE - Achmad Zainul Arifin (2020)
Sharia tourism has the potential to be developed given the large number of Muslims scattered throughout the world, especially Indonesia as a country whose majority population is Muslim. Then the challenge that arises is from the countries of the majority Muslim population in the world, only people in the Middle East region who most often travel and stay in hotels. This makes the emergence of Sharia-based hotel services to follow the trends of the Sharia market in order to attract local and foreign tourists to make purchasing decisions. So the purpose of this research is to find out, analyze, and prove whether there is an influence of promotion, service quality, and price on purchasing decisions. The method in this study is quantitative with a population of users or those who have ever transacted buying sharia-based hotel services on e-commerce sites. Samples taken as many as 100 respondents with simple random sampling method. And distributing questionnaires to users or those who have ever transacted buying sharia-based hotel services in e-commerce. The data analysis technique used is descriptive analysis and inferential analysis with the analytical tool used is SmartPLS 3.0 (Partial Least Square). The results showed that the promotion, service quality, and price variables significantly influence the purchasing decisions of Sharia-based hotel services on E-commerce sites.